Judge Sewall's apology : the Salem witch trials and the forming of an American conscience - Francis, Richard, 1945- (New York : Fourth Estate, 2005)
Biographer and novelist Francis looks at the Salem witch hunt of 1692 with fresh eyes, through the story of Samuel Sewall, New England Puritan, Salem trial judge, antislavery agitator, defender of Native American rights, utopian theorist, family man. The second-generation colonists were pitted against the pagan Native Americans and a hostile mother country intent on imposing control. Out of the struggle to maintain unity emerged the forces that drove the Salem tragedy. Five guilt-wracked years after pronouncing judgment, Sewall recanted the guilty verdicts, praying for forgiveness. This marked the moment when modern American values came into being--the shift from an almost medieval view of good and evil to a respect for the mysteries of the human heart. Drawing on Sewall's diaries, Francis shows us the early colonists as flesh and blood idealists, striving for a new society while coming to terms with the imperfections of ordinary life.--From publisher description.
Includes bibliographical references (p. [385]-395) and index.
Keywords: Sewall, Samuel, -- 1652-1730.; Sewall, Samuel, -- 1652-1730 -- Ethics; Puritans -- Massachusetts -- Biography; Judges -- Massachusetts -- Biography; Merchants -- Massachusetts -- Biography; Trials (Witchcraft) -- Massachusetts -- Salem; Massachusetts -- History -- Colonial period, ca. 1600-1775.; Salem (Mass.) -- History -- Colonial period, ca. 1600-1775.